Knowledge System Development Insights from Indonesia and International Applications - Hertz, Jana; Wulandari, Primatia Romana; Prasetiamartati, Budiati (RTI Press Publication, 2022)
Knowledge System Development: Insights from Indonesia and International Applications illustrates how knowledge systems work in the evidence-based policy making process and the dynamics of different actors in the ecosystem. Applying the Knowledge System Model 2.0 in Indonesia and in selected international case studies, it explores key issues and dynamics in the knowledge-to-policy process in Indonesia and offers important insights for application in other country contexts. Written from the unique vantage point of knowledge system actors themselves in cooperation with development practitioners and researchers, the book captures efforts to clarify the roles of different actors in the knowledge system and how they interacted to influence policy. When the actors and institutions in the knowledge system interact and challenge each other to articulate and commit to a shared purpose, it is easier to navigate the inherent tensions between technical solutions and political objectives to advance the reform agenda. Intermediaries in the knowledge system can play an important role in facilitating the interactions between these actors and institutions.